The study on the impact of constant power load to a direct current power system driven by photovoltaic, wind thyristor rectifier and liner sources - Halim, Mohd Jundullah (2013)
The phenomenon of instability is a major concern in DC power system. This phenomenon is contributed by the undesirable interaction between converter sourceload as well as the behaviour of the power electronic loads which behave as a constant power load. This phenomenon occurs since each converter has its internal control function to regulate the output voltage. As a consequence, the converter tends to draw a constant power which produces negative incremental input impedance within its bandwidth, in which can lead the instability in the DC power system. The effect of constant power load to a DC power system driven by photovoltaic (PV), combination of wind and thyristor rectifier and also linear sources have been examined in this project. The effects of constant power load (CPL) to a DC power system was extensively reviewed and examined through simulation using MATLAB simulation software. The higher the power level of CPL used, more severe effects on the DC bus system is observed especially when it been driven by the wind energy sources. Simple compensation method using RC parallel passive damping network was proposed and the simulation on a DC power system driven by linear sources shows that the system managed to gain stability under steady state condition.